Metabolic response assessment with 18F-FDG-PET/CT is superior to modified RECIST for the evaluation of response to platinum-based doublet chemotherapy in malignant pleural mesothelioma. Issue 86 (January 2017) - Kanemura, Shingo; Kuribayashi, Kozo; Funaguchi, Norihiko; Shibata, Eisuke; Mikami, Koji; Doi, Hiroshi; Kitajima, Kazuhiro; Hasegawa, Seiki; Nakano, Takashi
Highlights: 18F-FDG-PET/CT and mRESIST were used for tumour responsiveness evaluation in MPM. 29% of mRESIST stable disease (SD) patients were metabolic non-responders. Disease control rate was 93.9% and metabolic response rate was 71.9%. Progressive metabolic disease patients had lower time to progression. MRESIST stable disease (SD) patients should be further screened by 18F-FDG-PET/CT. Abstract: Purpose: Efficient monitoring of tumor responsiveness to chemotherapy is essential to mitigate high mortality risks and cytotoxic effects of chemotherapeutics. However, there is no consensus on the most suitable diagnostic technique/parameters for assessing response to chemotherapy in malignant pleural mesothelioma (MPM). We compared the tumor responsiveness of MPM patients as assessed using modified RECIST (mRECIST) criteria and integrated 18F-FDG-PET/CT. Methods: Histologically confirmed MPM patients (N = 82) who were treated with three cycles of cisplatin and pemetrexed, or carboplatin and pemetrexed, were included. mRECIST and integrated 18F-FDG-PET/CT were used to evaluate MPM tumor response to chemotherapy. Metabolic non-responders were defined as those with a 25% or greater increase in SUVmax compared with the previous value. Time to progression (TTP) and overall survival (OS) were compared between metabolic-responders and non-responders. Results: After three cycles of chemotherapy, 62(75.6%) of the patients were classified as having SD, 15 (18%) with partial remission (PR), and 5 (6%) with progressive disease (PD), based on mRECIST criteria. The cumulative median OS was 728.0 days (95% confidence interval [CI]: 545.9–910.1) and cumulative median TTP was 365.0 days (95% CI: 296.9–433.1). For the 82 patients, the disease control rate was 93.9%, whereas the metabolic response rate was only 71.9% (p < 0.001). All PD and PR patients were found to be metabolic responders on 18F-FDG-PET/CT; however, among the 62mRECIST SD patients, 18 (29%) were classified as metabolic non-responders. The median TTP for metabolic responders was 13.7 months, while it was 10.0 months for non-responders(p < 0.001). Metabolic responders had a trend toward longer OS, although the difference did not reach statistical significance (metabolic responders:33.9 months; non-responders: 21.6 months; p > 0.05). Conclusion: Several mRECIST-confirmed SD MPM patients may be classified as metabolic non-responders on18F-FDGPET/CT. Metabolic response is significantly correlated with the median TTP, suggesting it should be included in the evaluation of the response to chemotherapy in MPM patients classified as mRECIST SD, to identify non-responders.